2022
DOI: 10.3389/ftox.2021.787360
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Signaling Synergizes with TLR/NF-κB-Signaling for Induction of IL-22 Through Canonical and Non-Canonical AhR Pathways

Abstract: Interleukin 22 (IL-22) is critically involved in gut immunity and host defense and primarily produced by activated T cells. In different circumstances IL-22 may contribute to pathological conditions or act as a cancer promoting cytokine secreted by infiltrating immune cells. Here we show that bone marrow-derived macrophages (BMM) express and produce IL-22 after activation of the aryl hydrocarbon receptor (AhR) when cells are activated through the Toll-like receptor (TLR) family. The additional activation of Ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Alvarado et al found that enteropathogenic E. coli or inflammatory stimuli, such as dextran sodium sulfate, activated AhR via indoleamine 2,3-dioxygenase 1 (IDO1), which increased the resistance to enteropathogenic E. coli infection and colitis ( 30 ). Another study indicated that macrophages expressed and produced interleukin (IL)-22 after activation of AhR when cells were activated by the Toll-like receptor (TLR) family ( 31 ). The main virulence factor of E. coli , lipopolysaccharide (LPS), directly activated AhR, which in turn limits the LPS-induced inflammatory response in macrophages ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alvarado et al found that enteropathogenic E. coli or inflammatory stimuli, such as dextran sodium sulfate, activated AhR via indoleamine 2,3-dioxygenase 1 (IDO1), which increased the resistance to enteropathogenic E. coli infection and colitis ( 30 ). Another study indicated that macrophages expressed and produced interleukin (IL)-22 after activation of AhR when cells were activated by the Toll-like receptor (TLR) family ( 31 ). The main virulence factor of E. coli , lipopolysaccharide (LPS), directly activated AhR, which in turn limits the LPS-induced inflammatory response in macrophages ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…This PM2.5 contains many endotoxins compared with CRM28, and we previously reported that not only PAHs contained in urban PM2.5 but also endotoxins induce inflammatory reactions [ 35 ]. In addition, we suggested the crosstalk of AhR pathway and Toll-like receptor pathway [ 36 ]. Therefore, the deterioration of prognosis observed here may be due to endotoxins in addition to PAHs in urban PM2.5.…”
Section: Discussionmentioning
confidence: 99%
“…As AhR is highly expressed in a number of immune cells, AhR signaling plays important roles in the immune system in health and disease, and provides a molecular pathway to integrate the environment and metabolism in the immune responses [ 46 ]. In particular, ligand-activated AhR induces NF-κB-dependent transcription of inflammatory cytokines and chemokines [ 23 , 47 ], and may be linked with obesity and obesity-induced peripheral and central inflammation [ 48 ]. Various studies, including human cohort studies, support that inhibition of the AhR pathway or aberrant AhR activation may be a good therapeutic strategy for metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%